Bioresponsive carbon nano-gated multifunctional mesoporous silica for cancer theranostics - Prasad, Rajendra; Aiyer, Sandhya; Chauhan, Deepak S.; Srivastava, Rohit; Selvaraj, Kaliaperumal (Nanoscale, 2016)
Designing bioresponsive nanocarriers for controlled and efficient intracellular drug release for cancer therapy is a major thrust area in nanomedicine. With recent recognition by the US FDA as a safe material for human trials, mesoporous silica nanoparticles (MSNPs) are being extensively explored as promising theranostic agents. Green fluorescent carbon quantum dots (CQDs), though known as possible alternatives for their more toxic and relatively less efficient predecessors, are less known as gate keepers for drug release control. We report for the first time an efficient bioresponse of CQDs when judiciously designed using glutathione cleavable (redox responsive) disulphide bonds. When the anticancer drug doxorubicin loaded MSNPs are capped with these CQDs, they display promising drug release control on exposure to a mimicked intracellular cancer environment. Their dual functionality is well established with good control on preventing the premature release and exceptional bio-imaging of HeLa cancer cells. Fluorescence images prove selective targeting of HeLa cells by overexpression of folate receptors from the surface functionalised folic acid ligand. Extensive characterisation using XRD, TEM, BET analysis, drug loading tests, drug release kinetics, MTT assay and fluoroscence cell imaging helps in understanding the multi-functionalities of the successful design, extending its scope with exciting prospects towards non-invasive targeted drug delivery and bio-imaging for effective cancer diagnosis and treatment.

NIR light-triggered shrinkable thermoresponsive PNVCL nanoshells for cancer theranostics - Chauhan, Deepak S.; Singaravelu, Indulekha; Gottipalli, Rupesh; Reddy, B. Pradeep K.; Chikate, Tanmayee; Gupta, Ramkrishn; Jahagirdar, Dushyant N.; Prasad, Rajendra; De, Abhijit; Srivastava, Rohit (RSC Advances, 2017)
For the localized treatment of a tumor in a more controlled fashion, several stimuli-responsive nanocarriers and minimally or non-invasive techniques like photothermal therapy (PTT) have emerged. However, PTT is limited to only treatment of small and superficial tumors due to the inability of NIR light to penetrate more and kill the core cells of large and deep-seated tumors. As a preliminary step towards addressing the problem, NIR light-triggered thermoresponsive theranostic nanoshell consisting of chitosan-grafted poly(N-vinyl caprolactam) as core and biocompatible gold as shell (Au PNVCL NS) are synthesized and well characterized by various techniques. PNVCL is polymerized from N-vinyl caprolactam using free radical polymerization method, and chitosan is grafted to raise its lower critical solution temperature (LCST) to hyperthermic temperature (∼43 °C). Surface plasmon resonant gold shell over PNVCL NPs core is assembled by ascorbic acid-driven in situ reduction. Core to shell diameter ratio is controlled to tune the peak in NIR region (750 nm). Therapeutic potential of Au PNVCL NS is determined over breast cancer cells MCF-7, while diagnostic potential is compared with the commercial contrast agent-Omnipaque.

Disintegrable NIR light triggered gold nanorods supported liposomal nanohybrids for cancer theranostics - Chauhan, Deepak S.; Prasad, Rajendra; Devrukhkar, Janhavi; Selvaraj, Kaliaperumal; Srivastava, Rohit (Bioconjugate Chemistry, 2018)
In this work, facile synthesis and application of targeted, dual therapeutic gold nanorods-liposome (GNR-Lipos) nanohybrid for imaging guided photothermal therapy and chemotherapy is investigated. The dual therapeutic GNR-Lipos nanohybrid consists of GNR supported, and doxorubicin (DOX) loaded liposome. GNRs not only serve as a photothermal agent and increase the drug release in intracellular environment of cancer cells, but also provide mechanical strength to liposomes by being decorated both inside and outside of bilayer surfaces. The designed nanohybrid shows a remarkable response for synergistic chemophotothermal therapy compared to only chemotherapy or photothermal therapy. The NIR response, efficient uptake by the cells, disintegration of GNR-Lipos nanohybrid, and synergistic therapeutic effect of photothermal and chemotherapy over breast cancer cells MDA-MB-231 are studied for the better development of a biocompatible nanomaterial based multifunctional cancer theranostic agent.

In vivo examination of folic acid-conjugated gold-silica nanohybrids as contrast agents for localized tumor diagnosis and biodistribution - Prasad, Rajendra; Agawane, Sachin B.; Chauhan, Deepak S.; Srivastava, Rohit; Selvaraj, Kaliaperumal (Bioconjugate Chemistry, 2018)
Enhanced biocompatibility of nanosized contrast agent with high radiodensity and specific biodistribution is an important parameter for localized tumor imaging and organ safety. Various nanoparticles, especially gold nanorods (GNRs), have been applied for tumor diagnosis. However, their toxicity, nonspecific biodistribution, and easy aggregation are critical issues in cancer medicine. To avoid these issues, encapsulation of the GNRs in the core of nanoscopic mesoporous silica (MS) under ambient conditions, yielding multifunctional nanomaterials for cancer nanomedicine, is a recent and active development. Interestingly, GNR embedded MS nanohybrid (GNR-MS), though a promising material in nanomedicine, is rarely examined for tumor diagnosis, in vivo toxicity, organ safety, contrast ability, and excretion. Herein, we report a systematic in vivo examination of folic acid functionalized GNR-MS (GNR-MS-FA) for localized 4T1 breast tumor diagnosis, organ safety, and excretion using a one-time dose administration. The nanomaterials show good aqueous dispersibility, biocompatibility, high radiodensity, and tumor specific targeting ability (in vitro as well as in vivo). The in vivo tumor diagnosis and specific biodistribution of injected nanomaterials clearly demonstrates their potential for the visualization of tumors deep in the body of mice. In addition, all organs including the healthy glomerulus of the kidney are observed to be free of tissue injuries thereby indicating the superior biocompatibility of the nanomaterials.

Graphene oxide supported liposomes as red emissive theranostics for phototriggered tissue visualization and tumor regression - Prasad, Rajendra; Yadav, Amit S.; Gorain, Mahadeo; Chauhan, Deepak S.; Kundu, Gopal C.; Srivastava, Rohit; Selvaraj, Kaliaperumal (ACS Applied Bio Materials, 2019)
Selective tissue visualization and localized tumor regression without affecting the surrounding healthy tissues are critical concerns in cancer nanomedicine. Importantly, the complete wrapping of a flimsy matrix like liposome by multifunctional graphene oxide is an interesting engineering idea for nanomedicine design. Moreover, designing a safe and biodegradable nanohybrid with significant theranostic ability is a current need for targeted combined therapies. Here, we report a comprehensive result of in vivo tumor diagnosis and phototriggered tumor regression using a biodegradable red emissive nanotheranostic system, viz., graphene oxide flakes fortified liposome (GOF-Lipo), functionalized with folic acid (FA): GOF-Lipo-FA. Graphene oxide support enhances the stability of drug-loaded liposomes in an extracellular environment that prevents the premature release of loaded anticancer drug from the liposomal cavity. Promising outcomes of tumor regression (∼300 to 25 mm3) from organized cellular and animal studies are demonstrated in this work. These studies reveal superior biocompatibility, deep intracellular localization, 4T1 breast tumor diagnosis, and long time tumor binding ability of an injected emissive nanohybrid. Overall, a single dose of designed multifunctional systems demonstrates the best tumor regression.